Theoretical DFT study of Cannizzaro reaction mechanism: A mini perspective - Suhail, Mohammad; Mukhtar, Sofi Danish; Ali, Imran; Ansari, Ariba; Arora, Saiyam (European Journal of Chemistry, 2020)
In regards to the Cannizzaro reaction and its peculiar mechanism, some researchers have presented a free radical mechanism for the Cannizzaro reaction, while others have found that it is feasible through an ionic mechanism, but the actual mechanism has not been finalized yet. The researchers have given the proof of both the mechanisms through their papers published. Actually, Cannizzaro reaction may occur through both mechanisms depending on both molecular structure and different conditions which are yet to be explained. Recently published papers describe that free radical mechanism occurs only in a heterogeneous medium, while an ionic mechanism occurs in a homogeneous medium. We revealed no explanation of the molecular structure-based reason, responsible for a radical or an ionic mechanism. The present paper reviews not only homogeneous/heterogeneous medium conditions but also molecular structure-based facts, which may be responsible for the Cannizzaro reaction to occur through the radical or ionic mechanism, and that may be acceptable to the scientific society. Besides, Density Functional Theory study using Gaussian software was also involved in the explanation of the molecular structure, responsible for one of the two mechanisms. Also, the present paper specifies all points related to future perspectives on which additional studies are required to understand the actual mechanism with a definite molecular structure in the different reaction media.